(Fluoro)quinolone prescriptions for upper respiratory tract infections in the German outpatient sector: a health insurance claims analysis - Arens, Birgit; L’hoest, Helmut; Wolf, Alissa; Hennig, Beata; Marschall, Ursula; Nachtigall, Irit (GMS Infectious Diseases)
Background: Acute upper respiratory tract infections (URTIs) are frequent causes of medical treatment by general practitioners (GPs). In general, these are viral and self-limiting illnesses, but antibiotics are prescribed. In Germany, fluoroquinolones are not authorised for the indications pharyngitis, laryngitis, tonsillitis and acute bronchitis due to possible serious side effects. This analysis looks at fluoroquinolone prescriptions for URTI by GPs in 2022. Methods: Frequency of fluoroquinolone prescriptions were analysed at case level and regionally using administrative insurance data from the German health insurance company BARMER. We included patients treated in GP practices without relevant concomitant diseases. Results: In 2022, 25% (1,197,568/4,720,786) of insured persons with upper respiratory tract infections (URTI) were prescribed antibiotics. After excluding comorbidities and other risk factors such as previous hospitalisation, the prescription rate for uncomplicated URTIs was calculated to be 6% (80,786/1,365,646). Fluoroquinolones were given in 2.4% of antibiotic prescriptions (1,951/80,786). Nationwide, 3.7% of the GPs prescribed fluoroquinolones, most frequently in the region Brandenburg with 6.6% (74/1,121). Conclusion: This analysis showed that fluoroquinolones are still prescribed for uncomplicated URTI, which must be considered as alarming regarding the nature of the disease and the unfavourable risk-benefit profiles. There were clear regional differences in fluoroquinolone prescribing, indicating potential for improvement in the use of reserve antibiotics for uncomplicated upper respiratory tract infections.